2016
DOI: 10.1007/s40830-015-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Slip Resistance of Ti-Based High-Temperature Shape Memory Alloys

Abstract: Titanium with Nb, Zr, and Ta alloying substitutions possesses high plastic slip resistance and high transformation strains upon bcc (b) to orthorhombic ða 00 Þ transformation. In the current study, we determine the critical resolved shear stress (CRSS) for slip in Ti alloyed for a wide composition range of Nb, Ta, and Zr. The CRSS is obtained with a proposed Peierls-Nabarro formalism incorporating the generalized stacking fault energy barrier profile for slip obtained from the first-principles Density Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
5
11
0
Order By: Relevance
“…For complete details on lattice constant calculations, see Ref [10]. Table 1 represents the complete list of equilibrium lattice constants of Ti-Nb-Ta alloys considered in the present analysis.…”
Section: Lattice Constant Calculationsmentioning
confidence: 99%
See 4 more Smart Citations
“…For complete details on lattice constant calculations, see Ref [10]. Table 1 represents the complete list of equilibrium lattice constants of Ti-Nb-Ta alloys considered in the present analysis.…”
Section: Lattice Constant Calculationsmentioning
confidence: 99%
“…These alloys can also be exploited in biomedical applications [7,8] removing the concerns with the use of nickel element in human body. Several experiments [1,2,6,9], and recent theoretical calculations [10] have shown that upon alloying Ti-alloys with Nb, Ta, and Zr, high transformation strains (11 %) and high-martensite slip resistance can be achieved in addition to the high transformation temperatures (over 400 K). There are four other parameters such as transformation stress, twinning stress, martensite slip stress, and austenite slip stress that govern the shape memory and superelastic behavior.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations